Analisis Kesadaran dan Pemahaman Masyarakat dalam Membayar Zakat Pertanian Desa Rasabou Kecamatan Sape - Nurmaesyarah; Rafiuddin; Ismail (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to answer the question, namely what is the level of public understanding of the concept of agricultural zakat and what is the level of public awareness in paying agricultural zakat. This type of research uses a descriptive qualitative method which displays data as it is in the field and analyzes events, phenomena or social conditions. Data collection techniques are through observation, interviews and documentation. The results of the research show that the level of public awareness and understanding is still very low, and regarding agricultural zakat, the public's minimal knowledge regarding agricultural zakat means that the majority of agricultural zakaters never pay agricultural zakat, including people who can afford it and only do alms when harvesting or when they get more sustenance. So it can be said that the level of public awareness and understanding is still very low. Examining factors that influence public awareness, such as education and the influence of religious figures. Reorganize educational programs involving zakat institutions, government and community organizations to increase awareness and understanding of agricultural zakat.